Hybrid diphosphorus ligands in rhodium catalysed asymmetric hydroformylation - Chikkali, Samir H.; van der Vlugt, Jarl Ivar; Reek, Joost N. H. (Coordination Chemistry Reviews, 2014)
This review aims to illustrate recent advances in the application of hybrid diphosphorus ligands for the Rh catalysed hydroformylation of alkenes, discussing the most prevalent classes of hybrid systems, i.e. phosphine-phosphinite, phosphine-phosphonite, phosphine-phosphite, phosphite-phosphoramidite and phosphite-phosphoramidite and comparing their performance with relevant C-2 symmetric counterparts. In order to introduce the field and put the results in context, a short overview on Rh hydroformylation is provided. Available spectroscopic (in situ) data on the coordination modes of hybrid phosphorus ligands and the catalytic performance of these systems in asymmetric hydroformylation of vinyl arenes are reported. Potential avenues for future research are shortly discussed. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Asymmetric hydroformylation; Catalyst resting state; Hybrid ligand design; In situ spectroscopy; Rhodium